2009
DOI: 10.21273/hortsci.44.1.40
|View full text |Cite
|
Sign up to set email alerts
|

Leaf Blotching in Caladium (Araceae) Is Under Simple Genetic Control and Tightly Linked to Vein Color

Abstract: Cultivated caladiums (Caladium ×hortulanum Birdsey) are valued as important pot and landscape plants because of their bright, colorful leaves. Improving leaf characteristics or generating new combinations of these characteristics has been one of the most important breeding objectives in caladium. A major leaf characteristic in caladium is leaf blotching, the presence of numerous irregularly shaped color areas between major veins on leaf blades. This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…Previously, Harbaugh (2006, 2009) reported that leaf blotching in caladium is controlled by a single nuclear locus (B), with the leaf blotching allele (B) dominant over the non-blotching allele (b) and the leaf main vein color in caladium is controlled by another single nuclear locus (V), with the red allele (V r ) > white allele (V w ) > green allele (V g ). Deng and Harbaugh (2009) also demonstrated that the B and the V locus in caladium are closely linked. The genotype of 'Tapestry' at these two loci is BV g //bV r (Cao and Deng, unpublished), based on phenotyping a large number of progeny from the crosses between 'Tapestry' [blotched (Bb) and red-veined (V g V r )] and other cultivars or breeding lines [non-blotched (bb) and green-veined (V g V g )] and finding that the majority of progeny were blotched and greenveined or non-blotched and red-veined and that the allele B is in coupling phase with V g , and b is in coupling phase with V r .…”
Section: Discussionmentioning
confidence: 88%
“…Previously, Harbaugh (2006, 2009) reported that leaf blotching in caladium is controlled by a single nuclear locus (B), with the leaf blotching allele (B) dominant over the non-blotching allele (b) and the leaf main vein color in caladium is controlled by another single nuclear locus (V), with the red allele (V r ) > white allele (V w ) > green allele (V g ). Deng and Harbaugh (2009) also demonstrated that the B and the V locus in caladium are closely linked. The genotype of 'Tapestry' at these two loci is BV g //bV r (Cao and Deng, unpublished), based on phenotyping a large number of progeny from the crosses between 'Tapestry' [blotched (Bb) and red-veined (V g V r )] and other cultivars or breeding lines [non-blotched (bb) and green-veined (V g V g )] and finding that the majority of progeny were blotched and greenveined or non-blotched and red-veined and that the allele B is in coupling phase with V g , and b is in coupling phase with V r .…”
Section: Discussionmentioning
confidence: 88%
“…'Sea Foam Pink' originated from a cross between 'Carolyn Whorton' and 'Miss Muffet' that was made in Bradenton, FL, in Summer 2005 to investigate the mode of inheritance for their leaf spots (in 'Miss Muffet') and blotches (in 'Carolyn Whorton') (Deng and Harbaugh, 2009;Deng et al, 2008a). Both 'Carolyn Whorton' and 'Miss Muffet' are nonpatented commercial cultivars.…”
Section: Originmentioning
confidence: 99%
“…In caladium, the yellow leaf background color is controlled by a single dominant allele (LEM) and is tightly linked (3 to 4 cM) to the nonspotting allele (s) (Cao et al, 2017). The yellow leaf background color allele is expected to be tightly linked to the nonblotching allele (b) (Deng and Harbaugh, 2009). These genetic linkages may have led to the scarcity of commercial cultivars with yellow leaf background color and leaf spots or blotches.…”
mentioning
confidence: 99%
“…Cultivated caladium is an ornamental aroid produced for container or hanging basket plants or grown in landscapes for their variably shaped, colorful foliage. The ornamental value of caladium plants, to a great extent, depends on their leaf characteristics (Deng and Harbaugh, 2009). Improving leaf characteristics or creating novel combinations has been a main objective in caladium breeding and new cultivar development (Wilfret, 1993).…”
mentioning
confidence: 99%
“…The presence or absence of leaf spots is controlled by a single locus S, with the S allele for spotting and the s allele for nonspotting (Deng et al, 2008). Similarly, leaf blotching is determined by a single locus (B) with a dominant allele B for blotching and a recessive allele b for nonblotching (Deng and Harbaugh, 2009). The knowledge gained over the last 25 years on trait inheritance has been valuable for selecting breeding parents and parental combinations and planning breeding populations in caladium.…”
mentioning
confidence: 99%